2011
DOI: 10.1186/1751-0147-53-50
|View full text |Cite
|
Sign up to set email alerts
|

The preference for water nipples vs. water bowls in dairy goats

Abstract: BackgroundPrevious studies have reported that the design of the water dispensers can influence the water intake in farm animals. Horses and dairy cows seem to prefer to drink from an open surface whereas sheep and pigs apparently prefer water nipples, probably because of the worse water quality in water bowls. The aim of the present study was to examine the preference of dairy goats for water nipples or water bowls.MethodsIn each of the two experiments (exp. 1, dry goats, exp. 2 lactating goats), 42 dairy goat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the present study restrictively-fed calves drank 1.1 L water per day within the first 3 weeks of life. We do not think that the water intake of young calves can be ignored, as even heavier ruminating adult goats have only a daily water intake of 2.4 L (Bøe et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study restrictively-fed calves drank 1.1 L water per day within the first 3 weeks of life. We do not think that the water intake of young calves can be ignored, as even heavier ruminating adult goats have only a daily water intake of 2.4 L (Bøe et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies on dietary roughage composition have revealed discernible effects on water intake behaviors, with the inclusion of spineless cactus notably diminishing water consumption via traditional drinkers [18]. Additionally, investigations into water preference modalities, such as water nipples versus water bowls, have yielded insights into the nuanced drinking patterns and water intake propensities among dairy goat populations [19]. Furthermore, scientific inquiries into the physiological responses and lactational performances of late-lactation dairy goats under heat stress conditions have unveiled a substantial augmentation in total water evaporation rates among heat-stressed goats vis-à-vis those reared under thermoneutral conditions [20].…”
Section: Nutritional Requirements Of High-performing Dairy Goatsmentioning
confidence: 99%
“…In temperate climates, the water intake for goats is reported to be 139 g/kg W0.75 at midpregnancy, and lactating goats need 1.28 kg of water to produce 1 kg milk (Giger and Gihad 1991). Bøe et al (2011) reported a clear reduction in water quality in water bowls. The water intake was higher from nipple drinkers than from water bowls as reported in a study by Bøe et al (2011) in goats, while water wastage was quite high in water nipples (23-27 % of water usage) and almost negligible from water bowls.…”
Section: Waterers and Feeders For Goat Shedsmentioning
confidence: 99%